Kappa angles in different positions in patients with myopia during LASIK - Qi, Hui; Jiang, Jing-Jing; Jiang, Yan-Ming; Wang, Li-Qiang; Huang, Yi-Fei (International journal of ophthalmology, 2016)
AIM： To investigate the difference in kappa angle between sitting and supine positions during laser-assisted in situ keratomileusis（LASIK）.·METHODS： A retrospective study was performed on395 eyes from 215 patients with myopia that received LASIK. Low, moderate, and high myopia groups were assigned according to diopters. The horizontal and vertical components of kappa angle in sitting position were measured before the operation, and in supine position during the operation. The data from the two positions were compared and the relationship between kappa angle and diopters were analyzed.· RESULTS： Two hundred and twenty-three eyes（56.5%） in sitting position and 343 eyes（86.8%） in supine position had positive kappa angles. There were no significant differences in horizontal and vertical components of kappa angle in the sitting position or horizontal components of kappa angle in the supine position between the three groups（P 〉0.05）. A significant difference in the vertical components of kappa angle in the supine position was seen in the three groups（P 〈0.01）. Differences in both horizontal and vertical components of kappa angles were significant between the sitting and supine positions. Positive correlations in both horizontal and vertical components of kappa angles（P 〈0.05） were found and vertical components of kappa angle in sitting and supine positions were negatively correlated with the degree of myopia（sitting position： r =-0.109; supine position： r =-0.172; P 〈0.05）.·CONCLUSION： There is a correlation in horizontal and vertical components of kappa angle in sitting and supine positions. Positive correlations in both horizontal and vertical components of kappa angle in sitting and supine positions till the end of the results. This result still needs further observation. Clinicians should take into account different postures when excimer laser surgery needs to be performed.